Antithrombin ‘DREUX’ (Lys114Glu): A Variant with Complete Loss of Heparin Affinity - Mushunje, Alec; Zhou, Aiwu; Huntington, James A.; Conard, Jacqueline; Carrell, Robin W. (Thrombosis and Haemostasis, 2002)
Here we report the finding of a new natural antithrombin mutation that confirms the critical contribution of lysine 114 to the binding of the core heparin pentasaccharide, with the replacement of lysine 114 by glutamate causing a complete loss in affinity. The variant was identified in a father and son, the father having been investigated for an episode of cerebral ischaemia associated with hypercholesterolaemia. The variant forms SDS-stable complexes with activated factor X (fXa) and its thermal stability and rate of factor Xa inhibition in the absence of heparin are identical to those of normal antithrombin. Normal antithrombin binds to the high affinity heparin pentasaccharide with a Kd of 1nM, as detected by a 45% change in intrinsic fluorescence, resulting in a 230-fold increase in rate of factor Xa inhibition. However, no change in fluorescence was detected for the variant when titrated with heparin or the heparin pentasaccharide, nor was there detectable activation towards factor Xa, indicating a complete loss of heparin binding.
Keywords: Antithrombin; heparin; thrombosis; mutant; serpin